KONSELING MEROKOK BERJENJANGTERAPI NON FARMAKOLOGI PADA PEROKOKLANSIA PEREMPUAN DI DATARAN TINGGI DIENG - Dwi Widiyaningsih Widiyaningsih (Poltekkes Kemenkes Denpasar, 2020)
Cold temperatures in fact become a fact why smoking behavior in the Dieng plateau is increasingly growing and cultivating, not only among adolescents, adults and even the elderly according to a survey conducted by researchers, 9 out of 10 elderly people smoke. Even more astonishing data are from 9 elderly people who smoke 3 of whom are elderly women. Smoking behavior among elderly women in the Dieng Plateau is even made as one of the tourist destination icons that often invites curiosity both foreign and domestic tourism, because it is taboo in society's view in general but instead it is used as one of the strategies to attract tourists. Elderly women smoke at first in the sacred event of cutting dreads because the social status of elderly women who smoke comes from a high social status but has an impact on the sustainability of smoking behavior which will certainly result in the emergence of various diseases and other losses due to smoking such as increased ISPA and heart disease suffered by a child whose mother smokes. Various government efforts in controlling smoking behavior have also been carried out and one of the efforts is by giving non-pharmacological therapy to smokers. The method in this activity is in-depth and tiered counseling to 17 respondents, after being grouped into 3 categories (wanting to quit smoking, wanting to reduce, and continuing to smoke) and giving non-pharmacological therapy is given based on their respective categories. In the group that wants to quit smoking the counseling given is motivational so that the smoker really wants to leave the cigarette with a success rate of 100%, for group respondents wanting to reduce the attainment of counseling is 65% while the group continues to smoke has not been reached because the success rate of counseling is still low at 12 % only.